Constructing a CDS-Based Network Backbone for Data Collection in Wireless Sensor Networks - Xiaoyan Kui; Yu Sheng; Huakun Du; Junbin Liang (International Journal of Distributed Sensor Networks)
Data collection is one of the most important operations in wireless sensor networks. Currently, many researches focus on using a connected dominating set to construct a virtual backbone for data collection in WSNs. Most researchers concentrate on how to construct a minimum connected dominating set because a small virtual backbone incurs less maintenance. Unfortunately, computing a minimum size CDS is NP-hard, and the minimum connected dominating sets may result in unbalanced energy consumption among nodes. In this paper, we investigate the problem of constructing an energy-balanced CDS to effectively preserve the energy of nodes in order to extend the network lifetime in data collection. An energy-balanced connected dominating set scheme named DGA-EBCDS is proposed, and each node in the network can effectively transmit its data to the sink through the virtual backbone. When constructing the virtual backbone in DGA-EBCDS, we prioritize selecting those nodes with higher energy and larger degree. This method makes the energy consumption among nodes more balanced. Furthermore, the routing decision in DGA-EBCDS considers both the path length and the remaining energy of nodes in the path; it further prolongs the lifetime of nodes in the backbone. Our conclusions are verified by extensive simulation results.